Increasing postpartum rate of vaccination with tetanus, diphtheria, and acellular pertussis vaccine by incorporating pertussis cocooning information into prenatal education for group B streptococcus prevention. Issue 51 (16th December 2015) - Cheng, Po-Jen; Huang, Shang-Yu; Su, Sheng-Yuan; Peng, Hsiu-Huei; Chang, Chia-Lin
Highlights: We compared postpartum Tdap vaccination rate using two implementation strategies. Tdap vaccination rate was 55.6% during the pre-intervention period. Tdap vaccination rate increased to 71.2% during the post-intervention period. Adding information into prenatal GBS program increased postpartum Tdap vaccination. Abstract: Background: To evaluate whether incorporating pertussis cocooning information into prenatal education for group B streptococcus (GBS) prevention increased postpartum rate of vaccination with tetanus, diphtheria, and acellular pertussis (Tdap) vaccine. Methods: We performed a retrospective pre-intervention/post-intervention study of postpartum women at a teaching hospital in Taiwan. We compared the frequency of Tdap vaccination during the pre-intervention (May 1, 2009 to December 31, 2010) and post-intervention (March 1, 2011–March 31, 2012) time periods. The clinical intervention was incorporation of pertussis cocooning information into prenatal education for GBS prevention to pregnant women presented during a prenatal visit at 35–37 weeks of gestation. Postpartum Tdap vaccination rate during the pre-intervention and post-intervention periods was compared. We also specifically examined group differences in the percentage of women who received postpartum Tdap vaccination to explore factors that influenced their decision regarding Tdap vaccine. Results: Tdap vaccination was more likely during the post-intervention period compared with the pre-intervention period (2268 of 3186 [71.2%] compared with 2556 of 5030 [55.6%]; p  < .001). Comparisons between each subgroup of pre-intervention and post-intervention women showed that incorporating pertussis information into prenatal education for GBS prevention was beneficial except for women of maternal age 30–34 years and women living in rural areas. Conclusions: Prenatal GBS screening activities represent an opportunity for healthcare providers to offer pertussis cocooning information to eligible pregnant women to improve rates of postpartum Tdap vaccination.